An Analysis of Quality Control on Defective Products at PT. Signore - Keke, Yulianti; ., Veronica; Putrianto, Vera; Basyar Azzuhri, Muhammad; Pratiwi Perwitasari, Erni; ., Yuliantini (KnE Social Sciences, 2023)
This research aimed to analyze the damaged products at PT. SIGNORE, Tangerang, Indonesia. A Fish Bone Diagram was drawn to determine the factor that causes defective products. Then, an action plan including the concept of the Five M checklist, 5W + 1H (What, Why, Where, When, Who, How) and seven new tools of the corrective action plan, labor, machinery, materials, methods and environment were developed. The purpose of this study was to analyze the damage to a product because the quality of a product greatly determines customers’ shopping experience and customer satisfaction with the quality standards of the product. The results of this study indicated that defective products usually occur due to poor quality control processes. Keywords: Quality control, customer satisfaction, cause and effect